PENGARUH RASA SALING PERCAYA DIANTARA KOLEGA TERHADAP PERILAKU BERBAGAI PENGETAHUAN: META-ANALISIS - Elita, Yessy (HUMANITAS (Jurnal Psikologi Indonesia), 2010)
Knowledge sharing is crucial for organizations in order to achieve competitive advantage. Recently, several researchers has tested correlation between trust and knowledge sharing, however each of the results found different correlation values. Therefore, it has been commited meta-analysis to get the true correlation value. This meta-analysis collects data from 20 studies that gives statistic information. The result of this study proves the hypothesis that there is relationship between trust and knowledge sharing. Trust always positively correlates with knowledge sharing.